Transfigurations of the Commonplace: Hirst’s Tumbler, Joyce’s Tap - Judith Woolf (Humanities, 2023)
One reason why the concept of the quotidian has proved elusive to critics of literature and the visual arts is that the commonplace in art and literature so often refuses to remain untransfigured, not least because of its power to confront us with the material detritus with which we surround ourselves and which we will eventually join. It is not surprising, then, that contemporary artists share a preoccupation with finding both mortality and transcendence in what John Wilmot, Earl of Rochester called “the lumber of the world.” In this paper, I shall consider how an early Damien Hirst mini-installation, consisting of a glass tumbler of water and a ping-pong ball, takes its only partly mocking place in a still life tradition going back to Roman xenia and seventeenth-century vanitas paintings, and to a related literary tradition typified by Thomas Hardy’s Under the Waterfall and James Joyce’s great prose aria to water all its forms in the Ithaca section of Ulysses.